The Efficacy of Long-Term Chinese Herbal Medicine Use on Lung Cancer Survival Time: A Retrospective Two-Center Cohort Study with Propensity Score Matching. (24th August 2021) - Xu, Li-Li; Zhang, Su-Fang; Wang, Yu-Li; Luo, Ying-Bin; Fang, Zhi-Hong; Fang, Yuan; Xu, Rong-Zhong; Guo, Peng; Wu, Jian-Chun; Li, Yan
Abstract : Objective . To explore the efficacy of long-term use of Chinese herbal medicine (CHM) on survival time of lung cancer. Methods . We conducted a retrospective cohort study on lung cancer patients. A propensity score matching (PSM) was performed to balance the covariates. Progression-free survival (PFS) was the primary endpoint and overall survival (OS) was the secondary endpoint. Patients who received CHM therapy from the initial date of diagnosis of lung cancer were included in the CHM group. Patients who were not treated with CHM during the same interval were categorized in the control group. A Cox regression model was used to explore the prognostic factors related to lung cancer. Hazard ratios of different subgroups were also analyzed. Results . A total of 1134 patients were included in our study: 761 patients were in the CHM group and 373 patients were in the control group. After PSM, the mPFS and mOS in the CHM group were 70.4 months and 129.1 months, respectively, while the mPFS and mOS in the control group were 23.8 months and 99.7 months, respectively. The results of survival analysis on each stage demonstrated that patients may benefit from the long-term CHM treatment especially for patients with early stage. One-year to ten-year progression-free survival rates in the CHM group were higher than those in the control group (p < 0.001 ). COX multivariate regression analysis indicated that CHM treatment, female, low age at diagnosis, early tumor stage, and surgery were independent protective factors against recurrence and metastasis of lung cancer. Subgroup analysis showed that CHM treatment could reduce the risk of recurrence and metastasis in each subgroup (p < 0.01 ). Conclusion . Long-term CHM treatment with the Fuzheng Quxie Formula, which can be flexibly applied in the course of lung cancer treatment, not only has a positive influence on the progression-free survival time of lung cancer patients, but also reduces the risk of recurrence and metastasis of lung cancer.